Census in India: From Colonial Strategy to Democratic Politics - Prakash Kumar Patel (Knowledgeable Research A Multidisciplinary Journal, 2025)
This study analyzes the social impact of British colonialism on Indian society. British rule adopted a "divide and rule" policy, dividing Indian society along the lines of religion, caste, and race. Texts like the Manusmriti perpetuated the caste system. Censuses, legal codification, and social classification exacerbated inequalities. Consequently, divisions in Indian society deepened and national unity was affected. This research demonstrates that colonial policies profoundly altered India's social consciousness and structure.